Proof of concept implementation of an enterprise service bus for health information exchanges - Zuniga, Philip Christian; Del Mundo, Joseph Benjamin; Felizmeno, Edgardo; Mendoza, Marie Jo-anne; Zuniga, Rose Ann (Philippine Engineering Journal [eJournal])
Integration of health systems is one of the biggest problem in eHealth today. There are a lot of systems, yet they were developed using different platforms and technologies, making them virtually impossible to connect. In this paper, we discussed how to implement an ESB as the integration platform for health data. We identified use cases and functional requirements. Logical and deployment architecture were developed, and actual proof of concept of an ESB is developed. Experiments were also done to determine the overhead caused by the ESB. Some of the functionalities of the ESB were examined to determine their individual overheads.